Cardiovascular Outcomes Among Older Individuals With Depression Prescribed Amphetamines: A Retrospective Cohort Study. Issue 12 (5th February 2022) - Latronica, James R; Tuan, Wen Jan; Clegg, Taylor J; Silvis, Matthew L; Bone, Curtis
Abstract: Background: Prescription amphetamines are utilized for treatment of depression in older adults, yet cardiovascular risks in this population are not well described. The purpose of this study is to evaluate risk of cardiovascular events among adults aged 65 and older with depression who were prescribed amphetamines. Methods: We conducted a retrospective matched cohort study utilizing the TriNetx database and statistical software. The 1:1 propensity score matching technique was performed using logistic regression to balance the baseline characteristics of the population. Inclusion criteria were a diagnosis of depression and age 65 years and older. We excluded individuals with an adverse cardiovascular event or diagnosis of attention deficit and hyperactivity disorder prior to enrollment. Individuals were followed from January 1, 2018 to December 31, 2020. Those prescribed an amphetamine were considered exposed and others served as controls. We used descriptive statistics and calculated risk ratios to assess the relationship between amphetamine prescriptions and cardiovascular events in these cohorts. Results: There were 4 434 included in the exposed cohort and 4 434 matched controls in the unexposed group. The cohort exposed to amphetamines had higher high-density lipoprotein along with lower low-density lipoprotein, total cholesterol, hemoglobin A1C, systolic blood pressure, and body mass index than the control group, but increased risk of cardiovascular events (risk ratio: 8.9; 95% confidence interval: 6.39, 12.48). Conclusions: Amphetamines offer potential benefits to people with depression; however, these data suggest increased risk of cardiovascular events among older individuals. Additional research is warranted to fully characterize risk among subpopulations of older adults and inform patient–provider decision making.